Pelatihan dan Sosialisasi Digitalisasi Ekonomi Pada Generasi Z Sebagai Upaya Untuk Menghadapi Era Industri 4.0: Training and Socialization of Economic Digitalization in Generation Z as an Effort to Face the Industrial Age 4.0 - Ramadhan, Rizal Furqan; Setiawan, Didik (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
In the current era, information technology is developing rapidly over time. So many fields integrate with information technology, especially the economic field. Advances in information technology have made competition in the economic sector increasingly stringent. Trading that used to be done using conventional methods can now be done digitally using information technology. With this significant technological development, there are many opportunities, including entrepreneurship or entrepreneurship. For this reason, it is essential to have a digital entrepreneurship activity that is packaged with training. The training carried out is in the form of Digital Entrepreneurship Training, which is a form of economic digitalization training, especially entrepreneurial economics in trading or buying and selling transactions. The material is presented in two forms: theoretical and practical. Theoretical material provides an overview from the beginning of the development of technology until this technology develops towards the industrial era 4.0. Practical material delivered by the resource person is more directed at using E-commerce and Marketplace. Training like this needs to be held to add insight to Generation Z about the importance of mastering technology media for business or business interests.